Pengembangan Sistem Informasi Sales Force Automation (SFA) Menggunakan Metode Prototyping Pada Branded IT Store Malang - Ageng Rama Wijaya; Yusi Tyroni Mursityo; Niken Hendrakusma Wardani (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
The rapid development in the business world, especially on the field of electronic selling requires good data management. Branded IT Store is one of the companies that sells electronic goods. Implementation in recording of sales transactions that are still manually managed, causes sales data can not directly connected with other data related to product and has no information about products given to the customers via online. Based on the problems, sales force automation information system provide solutions by developing a system that can solve the problem of sales transactions and facilitate customers to seek information via online. The development of this research uses prototyping method to make it easier for users to better understand the needs of users in the early stages. There is 1 iteration from the results of this study, resulting in 21 functional requirements and 1 non-functional requirement. The results of validation testing of this research are functions related to the management of product data, data management sales, employee data management, customer data management, and make purchases can run well and have valid results. The result of UAT shows that the system is 100% acceptable from the company where manager, seller and cashier as the tester. In the compatibility testing results there are minor issues in the web browser application from Internet Explorer 9 to 11, Firefox 58 web browser and BlackBerry web browser application with version 7.1 or earlier.